(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
This paper aims at analyzing the existing relations between the Spanish socialists and various left-wing political forces in Mexico between the Mexican revolution and 1982, when the psoe seized the power. The article reflects upon the reasons for a lack of consolidation of a socialist party in Mexico, despite the fact that this process was unconnected to the revolutionary cycle of communism during the short 20th century, as well as to the presence of numerous democratic anti-fascist refugees in Mexico, especially Spanish republicans.